Utilization of Baglog Waste and Pineapple Peel Compost in Bioremediation of Oil Waste Contaminated Soil - Pramesti, Ayu Dita; Fitrihidajati, Herlina (LenteraBio : Berkala Ilmiah Biologi, 2022)
Waste oil contains a mixture of hydrocarbons that highly toxic, carcinogenic, a pungent odor and if released to environment will reduce soil quality and be harmful to living things. Therefore, to reduce waste oil pollution, bioremediation is necessary. This study aims to determine 1) the quality of compost made from baglog waste and pineapple peel, 2) the effect of adding baglog waste and pineapple peel compost to reduce TPH levels, 3) type and concentration of compost that optimal in reducing TPH levels. This research was experimental using a completely randomized design (CRD) with two treatment factors, the type of compost including baglog waste, pineapple peel, and their combination and the compost concentration of 20%, 40%, and 60% with five repetitions so there were 45 samples. Parameters measured included 1) compost nutrient content of C, N, and C/N ratio, 2) percentage of TPH levels, and 3) percentage of decrease in TPH levels. Data from the compost quality test were analyzed descriptively quantitatively based on the compost quality according to Hardjowigeno. Data from the percentage of TPH degradation were analyzed using two-way ANOVA and continued with Duncan's test. The results showed that 1) the best compost quality is pineapple peel compost containing 0.21% C, 1.57% N, and 0.135 C/N ratio; 2) the addition of baglog waste and pineapple peel has an effect on reducing TPH levels; 3) type and concentration compost that optimal in reducing TPH levels is pineapple peel compost at 60% with a percentage reduction in TPH levels of 70.67%.